2003
DOI: 10.1592/phco.23.1.9.31916
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cyclooxygenase‐2 Inhibition: A Target in Cancer Prevention and Treatment

Abstract: A major goal in the area of cancer prevention and treatment is to make rational use of defined molecular targets in order to block carcinogenesis. Studies conducted in experimental animal models for many human cancers, including those of lung, skin, mammary gland, urinary bladder, colon, and pancreas, have demonstrated that carcinogenesis often may be inhibited by the administration of a highly diverse group of biologic and chemical agents. One very promising and well-studied target is cyclooxygenase (COX)-2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 147 publications
(211 reference statements)
0
28
0
10
Order By: Relevance
“…In another study, investigators have demonstrated that in nonsmall-cell lung cancer cell lines, the selective COX-2 inhibitors could also enhance the cytotoxicity of various anticancer agents [23] . Thus it is expected that the potentially synergistic combination of COX-2 inhibitors and chemotherapy will play an important role in the future treatment of colorectal cancer [24] . However, in 2000, the VIGOR study had suggested a signifi cantly increased risk of acute myocardial infarction when taking another COX-2 inhibitor, rofecoxib (trade names Vioxx, Ceoxx and Ceeoxx) [25] .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, investigators have demonstrated that in nonsmall-cell lung cancer cell lines, the selective COX-2 inhibitors could also enhance the cytotoxicity of various anticancer agents [23] . Thus it is expected that the potentially synergistic combination of COX-2 inhibitors and chemotherapy will play an important role in the future treatment of colorectal cancer [24] . However, in 2000, the VIGOR study had suggested a signifi cantly increased risk of acute myocardial infarction when taking another COX-2 inhibitor, rofecoxib (trade names Vioxx, Ceoxx and Ceeoxx) [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Decreased cancer risk may be attributable to NSAID-related inhibition of cyclooxygenase-2 (COX-2) expression and subsequent prostaglandin synthesis, enhancement of cellular immune response, or induction of apoptosis (17)(18)(19)(20). There have been few studies that address the role of analgesics in the chemoprevention of endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The tumorpromoting activities of COX-2 and its prostaglandins are mediated via several mechanisms, including conversion of procarcinogens to carcinogens, stimulation of tumor cell growth, prevention of apoptotic cell death, promotion of angiogenesis and immunosuppression (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Several reviews have summarized evidence that nonsteroidal antiinflammatory drugs (NSAID) and, in particular, selective COX-2 inhibitors, are potentially interesting in cancer therapy (2)(3)(4)(5)(6)11). However, the enthusiasm was recently hampered by evidence of cardiovascular side effects (increase in the incidence of myocardial infarction) when using COX-2 inhibitors during longterm treatments (12).…”
Section: Introductionmentioning
confidence: 99%